FOLFIRINOX as Initial Treatment for Localized Pancreatic Adenocarcinoma: A Retrospective Analysis by the Trans-Atlantic Pancreatic Surgery Consortium. (14th February 2022) - Janssen, Quisette P; van Dam, Jacob L; Doppenberg, Deesje; Prakash, Laura R; van Eijck, Casper H J; Jarnagin, William R; O' Reilly, Eileen M; Paniccia, Alessandro; Besselink, Marc G; Katz, Matthew H G; Tzeng, Ching-Wei D; Wei, Alice C; et al.
Abstract: Background: Large pragmatic studies of patients who received 5-fluorouracil with leucovorin, irinotecan, and oxaliplatin ([m]FOLFIRINOX) as initial treatment for localized pancreatic ductal adenocarcinoma (PDAC) are lacking. This study aimed to provide realistic estimates of oncologic outcomes in these patients. Methods: This international retrospective cohort study included all consecutive patients presenting with localized PDAC who received at least 1 cycle of (m)FOLFIRINOX as initial treatment in 5 referral centers from the United States and the Netherlands (2012-2019). Primary outcome was median overall survival (OS), calculated from the date of tissue diagnosis, assessed using Kaplan-Meier estimates. Log-rank test was used to compare OS between groups. A Cox proportional hazards regression model was used to assess prognostic baseline factors for OS. All statistical tests were 2-sided. Results: Overall, 1835 patients were included, of whom 958 (52.2%) had locally advanced (LA), 531 (28.9%) had borderline resectable (BR), and 346 (18.9%) had potentially resectable (PR) PDAC. The median number of (m)FOLFIRINOX cycles was 6 (interquartile range = 4-8). Subsequent treatment included second chemotherapy (12.9%), radiotherapy (49.0%), and resection (37.9%). The resection rate was 17.6% for LA, 53.1% for BR, and 70.5% for PR PDAC ( P  < .001). The margin-negative resection rate (>1 mm) was 55.2% for LA, 62.6% for BR, and 79.2% for PR PDAC ( P  < .001). The median OS was 18.7 months (95% confidence interval [CI] = 17.7 to 19.9 months) for LA, 23.2 months (95% CI = 21.0 to 25.7 months) for BR, and 31.2 months (95% CI = 26.2 to 36.6 months) for PR PDAC ( P  < .001). The median OS for 695 patients who underwent a resection was 38.3 months (95% CI = 36.1 to 42.0 months). Independent prognostic factors at baseline for worse OS were more advanced stage, worse performance status, baseline carbohydrate antigen (CA) 19-9 > 500 U/mL, and body mass index ≤18.5 kg/m 2 . Conclusions: This large international cohort study provides realistic estimates of resection rates and survival in patients with LA, BR, and PR PDAC who started (m)FOLFIRINOX treatment in PDAC referral centers.